IMPROVING STUDENTSâ€™ WRITING NARRATIVE TEXT THROUGH SPIN A STORY WRITING PROMPT - Wahyuni, Yani Tri; Apriliaswati, Rahayu; Salam, Uray (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research entitled â€œImproving Studentsâ€™ Writing Narrative Text Through Spin A Story Writing Promptâ€ was purpose to investigate how the use of Spin A Story Writing Prompt could improve studentsâ€™ writing in narrative text to the eighth grade students of SMP Islamiyah Pontianak in academic year 2018/2019. The method used is classroom action research. The subjects of this research were the eighth grade students in class VIII A. The result showed that studentsâ€™ problems in writing narrative text such as writing narrative text based on the generic structure, writing narrative text based on the correct language features in writing narrative text and studentsâ€™ attention to follow the lesson had been solved by using Spin A Story Writing Prompt as the teaching media. In collecting the data, the writer used observation checklist table, field note, and writing test. The research approach used in this research was cooperative learning. Based on the results, it can be concluded that: the Spin A Story Writing Prompt could be used as a media to improve studentsâ€™ writing on narrative text such as generic structure, language features in writing narrative text and studentsâ€™ attention to follow the lesson.Â Keywords : Improving, Narrative Text, Spin A Story Writing Prompt